Upaya Peran Mahasiswa KKN UGJ dalam Meningkatkan Minat Baca di SDN 2 Karangwangi Kabupaten Cirebon - Muhammad Farhat Luthfi; Najwa Aulia; Inel Kadefi; Zahratun Nazieha; Farel Maryam Aruman; Gina Fadilah; Fiyana Trijuni; Suci Adella Fatmawati; Intan Aprillyanti; Widyana Lestari; Fiska Noviana; Mutiara Triani; Meylina Safitri; DIva Fauziah; Iqlima Anindiya; Dewi Rara Santi; Ade Saefu Rohman; Lindan Alfarizi; Agustiyan Rizky; Rubian Saputra; Muhammad Ivan; Ilham Fauzian Andika; Mohammad Abim; Juan Dinar Pinasti; Kholidah; Mohd. Abi Rafdi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This community service activity, conducted by the Literacy-Thematic KKN students of Universitas Swadaya Gunung Jati at SDN 2 Karangwangi, aimed to improve students’ reading interest through structured literacy programs. Initial observations showed limited facilities, including the absence of a proper library, insufficient book collections, and an unrealized reading corner, while the School Literacy Movement (GLS) was not optimally implemented. To overcome these challenges, several activities were carried out such as writing stories inspired by books, book reviews, reading aloud, literacy-based projects, village literacy competitions, school literacy visits, and the establishment of a reading corner. The implementation of these programs increased students’ enthusiasm for reading and encouraged them to utilize available facilities. Furthermore, the activities fostered students’ creativity, as reflected in their literary works displayed on the reading corner board. The program also motivated the school to sustain literacy initiatives by appointing a responsible teacher and planning future improvements